Comparative evaluation of antibacterial activity of caffeic acid phenethyl ester and PLGA nanoparticle formulation by different methods - Arasoglu, Tulin; Derman, Serap; Mansuroglu, Banu (IOP PUBLISHING LTD, 2016)
The aim of the present study was to evaluate the antimicrobial activity of nanoparticle and free formulations of the CAPE compound using different methods and comparing the results in the literature for the first time. In parallel with this purpose, encapsulation of CAPE with the PLGA nanoparticle system (CAPE-PLGA-NPs) and characterization of nanoparticles were carried out. Afterwards, antimicrobial activity of free CAPE and CAPE-PLGA-NPs was determined using agar well diffusion, disk diffusion, broth microdilution and reduction percentage methods. P. aeroginosa, E. coli, S. aureus and methicillin-resistant S. aureus (MRSA) were chosen as model bacteria since they have different cell wall structures. CAPE-PLGA-NPs within the range of 214.0 +/- 8.80 nm particle size and with an encapsulation efficiency of 91.59 +/- 4.97% were prepared using the oil-in-water (o-w) single-emulsion solvent evaporation method. The microbiological results indicated that free CAPE did not have any antimicrobial activity in any of the applied methods whereas CAPE-PLGA-NPs had significant antimicrobial activity in both broth dilution and reduction percentage methods. CAPE-PLGA-NPs showed moderate antimicrobial activity against S. aureus and MRSA strains particularly in hourly measurements at 30.63 and 61.25 mu g ml(-1) concentrations (both p 0.05). In the reduction percentage method, in which the highest results of antimicrobial activity were obtained, it was observed that the antimicrobial effect on S. aureus was more long-standing (3 days) and higher in reduction percentage (over 90%). The appearance of antibacterial activity of CAPE-PLGA-NPs may be related to higher penetration into cells due to low solubility of free CAPE in the aqueous medium. Additionally, the biocompatible and biodegradable PLGA nanoparticles could be an alternative to solvents such as ethanol, methanol or DMSO. Consequently, obtained results show that the method of selection is extremely important and will influence the results. Thus, broth microdilution and reduction percentage methods can be recommended as reliable and useful screening methods for determination of antimicrobial activity of PLGA nanoparticle formulations used particularly in drug delivery systems compared to both agar well and disk diffusion methods.
Keywords: Caffeic acid phenethyl ester; PLGA; nanoparticle system; antimicrobial activity; INFLAMMATORY RESPONSE; ESCHERICHIA-COLI; MEDICAL SUTURES; CELLULAR UPTAKE; MURINE MODEL; IN-VITRO; PROPOLIS; ANTIOXIDANT; STAPHYLOCOCCUS; DELIVERY; Science & Technology - Other Topics; Materials Science; Physics